2016
DOI: 10.1111/nph.14045
|View full text |Cite
|
Sign up to set email alerts
|

Seedling growth responses to phosphorus reflect adult distribution patterns of tropical trees

Abstract: Soils influence tropical forest composition at regional scales. In Panama, data on tree communities and underlying soils indicate that species frequently show distributional associations to soil phosphorus. To understand how these associations arise, we combined a pot experiment to measure seedling responses of 15 pioneer species to phosphorus addition with an analysis of the phylogenetic structure of phosphorus associations of the entire tree community. Growth responses of pioneers to phosphorus addition reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 48 publications
5
91
4
1
Order By: Relevance
“…For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes. For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes. For example, Cernusak et al (2011) showed variation in the capacity for nodulation among tropical N 2 fixers, Nasto et al (2017) showed that differences in nutrient acquisition strategies between non-N 2 and N 2 fixers were driven by individual species belonging to each functional group, Zalamea et al (2016) and Png et al (2017) suggested that root phosphatase activity is phylogenetically constrained and not related to functional group or N 2 fixation, and Soper et al (2018) demonstrated a lack of a relationship between N 2 fixation, foliar N, and P acquisition among a variety of N 2 -fixing legumes, non-N 2 -fixing legumes, and non-legumes.…”
Section: Discussionmentioning
confidence: 99%
“…In the growing house experiment, species-specific growth responses to +P increase steadily with the strength of species-level associations with P-rich soils (Zalamea et al 2016). In the growing house experiment, species-specific growth responses to +P increase steadily with the strength of species-level associations with P-rich soils (Zalamea et al 2016).…”
Section: Experimental Evidence For Nutrient Limitationmentioning
confidence: 95%
“…The CO 2 concentration was prevented from overshooting by providing CO 2 in multiple pulses of 2 s interrupted by 5 s without CO 2 injection. Seedlings were watered daily and received 150 ml of a liquid fertilization treatment weekly (as in Zalamea et al, ). All seedlings received a full nutrient treatment including 4 mM KNO 3 , 1.5 mM MgSO 4 and 4 mM CaCl 2 , micronutrients and Fe as ethylenediaminetetraacetic acid iron (III) sodium salt.…”
Section: Methodsmentioning
confidence: 99%
“…While increasing P appears to stimulate growth rates for most tree species in lowland forests in Panama (Turner et al, ; Zalamea et al, ), low‐P levels do not necessarily imply a community‐wide limitation on productivity; rather, some species thrive on low‐P soils, while others dominate soils with higher P levels (Turner et al, ). In fact, Zalamea et al () showed that the growth of species naturally distributed in sites with high‐P availability was stimulated by P addition in a pot experiment, while species from low‐P availability sites have little or no change in growth when P was added. Furthermore, species distributional associations with soil P did not predict biomass allocation or foliar P when plants were grown at either low ‐ or high‐P (Zalamea et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation